Brief Psychotic Disorder During the National Lockdown in Italy: An Emerging Clinical Phenomenon of the COVID-19 Pandemic. (6th August 2020) - D′Agostino, Armando; D'Angelo, Simone; Giordano, Barbara; Cigognini, Anna Chiara; Chirico, Margherita Lorenza; Redaelli, Cristiana; Gambini, Orsola
Abstract: The impact of the COVID-19 pandemic on psychosis remains to be established. Here we report 6 cases (3 male and 3 female) of first-episode psychosis (FEP) admitted to our hospital in the second month of national lockdown. All patients underwent routine laboratory tests and a standardized assessment of psychopathology. Hospitalization was required due to the severity of behavioral abnormalities in the context of a full-blown psychosis (the Brief Psychiatric Rating Scale [BPRS] = 75.8 ± 14.6). Blood tests, toxicological urine screening, and brain imaging were unremarkable, with the exception of a mild cortical atrophy in the eldest patient (male, 73 years). All patients were negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) throughout their stay, but 3 presented the somatic delusion of being infected. Of note, all 6 cases had religious/spiritual delusions and hallucinatory contents. Despite a generally advanced age (53.3 ± 15.6), all patients had a negative psychiatric history. Rapid discharge (length of stay = 13.8 ± 6.9) with remission of symptoms (BPRS = 27.5 ± 3.1) and satisfactory insight were possible after relatively low-dose antipsychotic treatment (Olanzapine-equivalents = 10.1 ± 5.1 mg). Brief psychotic disorder/acute and transient psychotic disorder diagnoses were confirmed during follow-up visits in all 6 cases. The youngest patient (female, 23 years) also satisfied the available criteria for brief limited intermittent psychotic symptoms. Although research on larger populations is necessary, our preliminary observation suggests that intense psychosocial stress associated with a novel, potentially fatal disease and national lockdown restrictions might be a trigger for FEP.